(untitled) (Editora Impacto Científico, 2025)
A colostomy is an exteriorization of the colon through the abdominal wall, fixing it to the skin, with the aim of creating an artificial outlet for fecal contents. It can be temporary or permanent and is indicated in cases of colorectal cancer, diverticular disease, inflammatory bowel disease, anal incontinence, intestinal perforation or trauma. The important thing in preoperative care is to take early action on: self-care with the stoma, identifying the emotional state with the impact of the disease and expectations regarding self-esteem and body image. In the post-operative assessment, it is important to evaluate and observe the condition of the stoma in relation to its color and protrusion, with a view to detecting complications. Control and appearance of the intestinal effluent, as well as the adherence of the collecting equipment. Provide guidance on skin, stoma and device care to the patient and caregiver. It is important to keep up the follow-up in the late post-operative period, always reviewing and reinforcing specific self-care guidelines. It is important to observe the late complications of stomas.